Variability and trends in rainy season characteristics of the Eastern Cape - Mahlalela, Precious (Department of Oceanography, 2024)
Forming part of south-eastern South Africa, the Eastern Cape province has been prone to extreme weather events such as floods and droughts. The region also displays considerable interannual rainfall variability with a tendency towards prolonged dry periods in recent decades. There is generally a poor understanding of the factors contributing to this rainfall variability. This is concerning considering the recent prolonged (2015 - 2020) drought, that has had major socio-economic effects particularly on the large impoverished rural population as well as on some urban areas where supplied water services have broken down in several cases. Even with some rainfall relief in the province during 2022, water shortages persist, particularly in the largest metropolitan area of Nelson Mandela Bay. The region is influenced by both midlatitude and tropical systems leading to a complex regional meteorology that hitherto has not been much studied compared to other parts of South Africa. Here, variability and trends in rainfall characteristics for the Eastern Cape are examined. Focus is placed on the spring (September-November) and summer (December- February) as these seasons contribute the largest proportion to annual totals. The spring season contributes between about 25-35% of the annual rainfall total, while the summer season contributes about 40-45%. Due to limited available station data, the Climate Hazards Infrared Precipitation with Stations (CHIRPS) data set is used. Comparisons with the available station data, provides confidence in the CHIRPS-derived results. On interannual time scales, the results indicate that dry (wet) springs over the Eastern Cape are associated with a cyclonic (anticyclonic) anomaly southeast of South Africa as part of a shift in the zonal wavenumber 3 pattern in the midlatitudes. Over the landmass, a stronger (weaker) Botswana High is also apparent with increased (decreased) subsidence over and near the Eastern Cape which is less (more) favourable for cloud band development and hence reduced (enhanced) rainfall during dry (wet) springs. The summer season shows significant El Niño Southern Oscillation (ENSO) and Southern Annular Mode (SAM) influences as well as from the Botswana High. Composites show that dry (wet) summers tend to be associated with a negative (positive) SAM pattern superimposed with a wave number 4 anomaly. According to CHIRPS data, the spring season has shown a significant decreasing trend in total rainfall as well as the number of light, moderate, and heavy rainfall days over most of the province since 1981. The summer signal is less consistent, with a significant increase in rainfall in some inland areas but a decrease in rainfall near the coast which is not found to be statistically significant. The observed summer trends are attributed to an increase in light and moderate rainfall days inland and a decrease in heavy rainfall days near the coast. An examination of the regional rainfall features suggests that the observed decrease in spring rainfall may be related to an observed decrease in the number of cloud bands during the spring while, the observed increase in rainfall inland during the summer might be associated with increased ridging along the south coast. Analysis of mid-century (2040-2060) CMIP5 rainfall projections suggests that there may be a flattening of the annual cycle over the Eastern Cape with the winter becoming wetter and parts of the summer drier. There is a large spread in CMIP5 model projections over the region with the multi-model mean projecting a very slight drying in both seasons. It is suggested that existing climate models may find representing the Eastern Cape region particularly challenging given its sharp gradients in land surface and ocean conditions and its complex meteorology